Data reduction in comprehensive two-dimensional gas chromatography for rapid and repeatable automated data analysis - PM Harvey; Robert Shellie (2012)
A rapid approach for comprehensive two-dimensional gas chromatographic data analysis is introduced, providing important environmental metrics including total petroleum hydrocarbon concentration as well as chemical-class distribution. The approach, comprising transformation of exported data files to two-dimensional retention time arrays, blank subtraction, alignment and projection onto new axes, subdivision of the aligned two-dimensional data matrix, and compilation of summary data is able to be performed without user intervention. The approach satisfies critical goals of rapid batch analysis with repeatability and traceability. Application to assessment of petroleum hydrocarbon contaminated soil samples from Macquarie Island, a remote Southern Ocean island, is shown to illustrate the utility of this new data analysis strategy. © 2012 American Chemical Society.